CT and MRI of the abdomen and pelvis : a teaching file - Ros, Pablo R.; Mortele, Koenraad J.; Pelsser, Vincent; Thomas, Smitha (LWW Teaching File., 2014)
"Now in its Third Edition, this trusted and practical volume in LWW's Teaching File Series offers residents and practicing radiologists a unique opportunity to study alongside the experts in their field. For the first time, CT and MRI of the Abdomen and Pelvis is a hybrid publication, with a new paperback format and accompanying web content that includes a wealth of case studies users can access from their laptop, tablet, or mobile device. The book is useful both as a quick consult or study aid for anyone preparing for Board examinations in Radiology and other specialties where knowledge of CT and MRI of the abdomen and pelvis are required. This skill-builder delivers ... 416 structured case studies based on actual patients--each providing a brief patient history, as many as four CT/MR images, a short description of the findings, differential diagnosis, final diagnosis, and a discussion of the case. Detailed imaging of all areas of the abdomen and pelvis including the liver and biliary system, pancreas, GI tract, spleen, mesentery/omentum/peritoneum, kidney and urinary system retroperitoneum and adrenal glands and abdominal wall--helps readers understand relevant anatomy and identify pathologies. NEW to third Edition ... Hybrid format includes print and online components. 30% new cases address new challenges and provide timely information. Accompanying web site delivers access to all cases in the book, plus several hundred supplemental, "bonus" cases!"--Provided by publisher